[OP.1B.09] RELATIONSHIP BETWEEN CHA2DS2-VASC SCORE AND PRECLINICAL CARDIOVASCULAR ORGAN DAMAGE IN A GENERAL POPULATION IN NORTHERN ITALY: THE VOBARNO STUDY. (September 2016) - Paini, A.; Salvetti, M.; Agabiti Rosei, C.; Bertacchini, F.; Aggiusti, C.; Rubagotti, G.; Maruelli, G.; Agabiti Rosei, E.; Muiesan, M.L.
Abstract : Objective: Background: The CHA2DS2-VASc score is used in patients with atrial fibrillation (AF) for stroke risk stratification. Recent studies have shown that CHA2DS2-VASc is also predictive of cardiovascular (CV) events and mortality, whether or not AF is present. Few data are available on the relationship between CHA2DS2-VASc and preclinical organ damage (OD) in the general population. Design and method: Aim of our study: was to evaluate the relationship between CHA2DS2-VASc and 10 years Framingham risk scores and preclinical cardiac and vascular organ damage in subjects from a general population. Methods: A total of 478 subjects underwent clinical examination with blood pressure measurement (clinic and 24 hours), and laboratory examinations. Left ventricular (LV) and carotid artery structure were assessed by ultrasound and carotid-femoral PWV was measured. OD was defined according to ESH ESC 2013 Guidelines. CHA2DS2-VASc was calculated as recommended by current AF Guidelines. The Framingham risk score for cardiovascular events (FRS CVD), for stroke (FRS stroke) and for coronary heart disease (FRS CHD) were also calculated. Results: Results: mean age was 58 ± 10 (range 43–74 yrs), 44% were males, 69% hypertensives (37% treated). Left ventricular mass index, meanmax IMT and carotid-femoral pulse wave velocity (PWV) were significantly correlated with all the Framingham risk scores as well as with CHA2DS2-VASc (table). Figure. No caption available. The simultaneous inclusion of CHA2DS2-VASc and FRS (for CVD or Stroke or CHD) in linear regression analysis showed that the relationship between CHA2DS2-VASc and OD is independent of FRS. Conclusions: Conclusions: CHA2DS2-VASc score is significantly correlated to preclinical organ damage in patients from a general population.